Prevalence and Incidence of Injury during Olympic-style Shooting Events: A Systematic Review - Mica R. Harr; Cody J. Mansfield; Bailey Urbach; Matt Briggs; James Onate; Laura C. Boucher (International Journal of Sports Physical Therapy)
# Background